Transformasi Olahraga Daerah: Implementasi Pelatihan Wasit Bulu Tangkis di KEJURNAS Provinsi Gorontalo sebagai Kontribusi Inovatif Dosen - Irawan, Safri; Haryani, Meri; Prasetyo, Agung; Mile, Rifky; Suardika, I Kadek; Haryanto, Arief Ibnu; Wahyuni, Hera; Nurkhoiroh, Nurkhoiroh; Mile, Sarjan; Datau, Suriyadi; Syam, Asry (-, 2024)
This article discusses the implementation of badminton referee training conducted during the Provincial Gorontalo National Championship (KEJURNAS). The training aims to improve the competence and professionalism of local referees in leading matches, as well as to provide a positive contribution from lecturers to the development of regional sports. The training activities were carried out for two days at Hotel Rachmat, followed by an experience of refereeing matches at the TRISAKA Badminton Hall for four days until the final. This article examines the contributions of this training to the quality of refereeing and its impact on badminton in Gorontalo Province.